Nanoparticles sorting and assembly based on double-axicon in an optofluidic chip - Shi, Y. Z. (2014)
This paper presents a novel optofluidic system for nanoparticle sorting by using interference patterns generated through a double-axicon. The tightly confined Bessel beam is used to sort the 200-nm and 500-nm polystyrene nanoparticles massively and simultaneously by adjusting the flow rate and the laser power. Additionally, 2-μπι polystyrene particles are assembled into a 2D array by utilizing the discrete interference pattern. This system first utilizes the interference patterns based on the on-chip double-axicon, and integrates the sorting and assembly abilities into a single chip. It has a great potential in bacterial and DNA sorting and cell assembly.